2005
DOI: 10.1056/nejmoa044441
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation ofEchinacea angustifoliain Experimental Rhinovirus Infections

Abstract: The results of this study indicate that extracts of E. angustifolia root, either alone or in combination, do not have clinically significant effects on infection with a rhinovirus or on the clinical illness that results from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
138
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(141 citation statements)
references
References 19 publications
1
138
0
2
Order By: Relevance
“…9 A subsequent large, high-quality randomized controlled trial found no benefit of Echinacea angustifolia for the treatment of experimentally induced rhinovirus infection. 10 However, some authorities believe that a different species (Echinacea purpurea) or a higher dose of the species studied, would have been more likely to find an effect. 11 The herb is believed to be safe, with prior studies showing rates of side effects similar in Echinacea and placebo groups.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…9 A subsequent large, high-quality randomized controlled trial found no benefit of Echinacea angustifolia for the treatment of experimentally induced rhinovirus infection. 10 However, some authorities believe that a different species (Echinacea purpurea) or a higher dose of the species studied, would have been more likely to find an effect. 11 The herb is believed to be safe, with prior studies showing rates of side effects similar in Echinacea and placebo groups.…”
Section: Efficacymentioning
confidence: 99%
“…The most critical element will be to define specific standards for herbal products to ensure consistency between studies. Even recent studies (including the aforementioned study of Echinacea) 10 that used highquality methodology were open to criticism about the formulation of the herbal product used because no clear, wellestablished standard of the chemical fingerprint exists for most commonly used herbs. The effort to create standards for herbal products is most likely to be successful if supported and coordinated by an appropriately funded branch of the FDA.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, data are in conflict regarding its efficacy, with some studies supporting effectiveness (Goel et al 2005;Lindenmuth and Lindenmuth 2000;Schulten et al 2001) and others discounting it (Barrett et al 2002;Turner et al 2005;Yale and Liu 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Kesimpulan penelitian yang sama juga ditemukan pada penggunaan echinaceae dalam terapi rhinitis. [13][14][15][16] Lima koma tujuh persen orang tua memberikan jamu tradisional seperti tolak angin anak, jeruk nipis dan kecap, serta beras kencur. Kandungan dalam 17 Kandungan madu sendiri terbukti dapat mengurangi gejala batuk dan memperbaiki kualitas tidur anak pada malam hari.…”
Section: Pembahasanunclassified